Pengaruh Promosi, Harga, dan Kepuasan terhadap Loyalitas Pelanggan E-Commerce Shopee - Wibawa, Tegar; Wijaya, Shierli (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: This study aimed to determine the level of loyalty in the use of shopees as an online shopping platform among students of the 2020-2023 cohorts in Business Management at Pradita University. These aspects include promotion, pricing, and satisfaction. Research methodology: The approach used in this study is a quantitative approach to data collection using research tools. This study used a survey method and questionnaire techniques to collect data, which were processed using SPSS version 26. Results: The results show that promotion does not influence customer loyalty, whereas price and satisfaction influence customer loyalty. Promotion, price, and satisfaction influence customer loyalty simultaneously. Limitations: The limitation of this research is that distributing questionnaires via gform is not completely helpful; sometimes there are still some respondents who do not fill out the questionnaire as honestly as possible. Distributing questionnaires via form and offline will predominately not be completed by potential respondents. The satisfaction variable in this study is affected by the symptoms of heteroscedasticity. Contribution: The author advises that Shopee can increase customer loyalty by maintaining prices and satisfaction so that it can increase Shopee customer loyalty.